IMPACT OF SOCIAL MEDIA ON CRYPTOCURRENCY INVESTING DECISIONS – A BEHAVIORAL FINANCE PERSPECTIVE (Proceedings of the World Conference on Media and Mass Communication, 2023)
In Vietnam, many people are investing in cryptocurrency due to the hype on social media and Bitcoin's rapid growth. However, new investors often lack the necessary financial knowledge and skills to make wise decisions during times of extreme market volatility. This is where Behavioral Finance comes in. This field of study examines how traders and investors expose themselves to cognitive biases, leading to inefficiencies and anomalies in financial markets. To better understand the behavior and decision-making processes of cryptocurrency investors on social media, this research paper will use data mining and text-based analysis along with behavioral finance theory. By analyzing tweets, on Twitter related to cryptocurrency using Orange 3, we hope to uncover how investors react to information they receive from their peers and the market in general. This will provide guidance and essential information to help investors make wiser decisions and avoid emotional investing behavior. The implications of our findings will be especially helpful for short-term investors who need to gain knowledge and skills to navigate the market. Our research will also show that the principles of cryptocurrency investing do not necessarily follow traditional finance principles.
Keywords: Cryptocurrency, Bitcoin, social media, herding theory, prospect theory, heuristic theory, LUNA, Twitter